2022
DOI: 10.1101/2022.07.05.498860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting causal citations without full text

Abstract: Citation analysis generally assumes that each citation documents causal knowledge transfer that informed the conception, design, or execution of the main experiments. Citations may exist for other reasons. In this paper we identify a subset of citations that are unlikely to represent causal knowledge flow. Using a large, comprehensive feature set of open access data, we train a predictive model to identify such citations. The model relies only on the title, abstract, and reference set and not the full-text or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“… 23 Metascience studies suggest that the discrepancy between preprints and peer-reviewed articles is small and the quality of reporting is within comparable range, supporting the validity of communicating research findings in preprints before review. 24 , 25 The results of our study and others 24 , 25 , 26 , 27 , 28 , 29 , 30 suggest that the reliability of data reported in preprints is generally high. Although there are measurable effects on research articles after peer review, such as the observed reduction in CIs, effect sizes are small.…”
Section: Discussionsupporting
confidence: 63%
“… 23 Metascience studies suggest that the discrepancy between preprints and peer-reviewed articles is small and the quality of reporting is within comparable range, supporting the validity of communicating research findings in preprints before review. 24 , 25 The results of our study and others 24 , 25 , 26 , 27 , 28 , 29 , 30 suggest that the reliability of data reported in preprints is generally high. Although there are measurable effects on research articles after peer review, such as the observed reduction in CIs, effect sizes are small.…”
Section: Discussionsupporting
confidence: 63%